Microencapsulation of peppermint oil using an ionic gelation electrospray technique - Abdul Kalam, Azad; Doolaanea, Abd Almonem; Al-Mahmood, Sinan Mohammed Abdullah; Wan Sulaiman, Wan Azizi; Al-Ani, Imad Matloub Dally (2018)
INTRODUCTION: Alginate has become the material of choice for encapsulation by ionic gelation and widely used in engineering and biotechnological industries, due to its biocompatibility, low cost and being a non-toxic polymer. Peppermint oil have been used for many pharmaceutical formulations and currently used as pharmaceutical active ingredient for few specific diseases. OBJECTIVES: This study aims to encapsulate and characterize peppermint oil in alginate microbeads by electrospray technique. METHODS: In this study, sodium alginates, Lecithin, calcium chloride and peppermint oil were used consecutively as an encapsulating material, emulsifying or, stabilizing agent, gelling solution and, as an active pharmaceutical ingredient. The electrospray technique was employed to encapsulate the peppermint oil by preparing the microbeads. To characterize emulsion, emulsion stability, size distribution of emulsion oil droplets and zeta potential, microstructure and shape and size of beads was determined followed by centrifugation or accelerated technique, a light scattering instrument, and light microscope. Finally, the analytical method was validated followed by ICH_Q2 guideline and encapsulation efficiency was determined by using UV-vis spectrophotometric (600 nm) method. The method was validated for specificity, linearity, accuracy, precision, limit of detection, and limit of quantitation. RESULTS: For the analysis method, it was found that peppermint oil obeys linearity within the concentration range of 3 mg/ml - 25 mg/ml and coefficient correlation was found to be 0.9890. The proposed method was found to be specific while estimating commercial formulations without interference of excipients. The emulsion was found to be highly stable while the percentage of beads yield was about 88%. In addition, the distribution of particle size of the emulsion was almost in nano size. In the characterization of beads, the size and shape of the beads were in good spherical shape. CONCLUSION: The analytical method was found to be simple, sensitive, accurate, precise & the most important cost effective and can be used for quantifying peppermint oil in the beads. Furthermore, peppermint oil was successfully encapsulated in alginate microbeads.